IMPLEMENTASI KURIKULUM DALAM PEMBENTUKAN KARAKTER SISWA KELAS III SD TA’MIRUL ISLAM SURAKARTA - Warsito, Warsito Warsito; Samino, Samino Samino (Profesi Pendidikan Dasar, 2014)
The type of this research is a qualitative field research. The data collection used in thisresearch is observation method, interview, and documentation. In the qualitative descriptiveanalysis using inductive approach. The result of these research are; firstly; themanagement of curriculum in forming student’s character in Ta’mirul Islam ElementarySchool of Surakarta, consist of several points, there are: the process of learningcurriculum planning which consist of staff coordination meeting and early meeting bymaking learning administration. Secondly, implementing curriculum that forming somecharacter, such as discipline and responsible, in line with some good habituation likereciting a holy Qur’an, patriotism, obligatory, and sunnah prayer, doing exercise, theimplementation of student’s monitoring book, assignments, and charity and religiousactivities such as charity’s camp and pesantren ramadhan. Thirdly, the evaluation ofimplementation activities in forming the character that packed in supervision and monitoringactivities. The management of curriculum implementation which build third classin Ta’mirul Islam Elementary School of Surakarta is really affective and efficient, sothat many educational success can be reached in academic as well as in non-academicsector’s, especially in building discipline and responsible character. There are severaldifficulties that management of curriculum implementation face in building charactersuch as, the number of students, the students economic background, a little gap betweenschool and student’s parents, less communication, the distance of students homewith school, and some other student’s environment factors that unsupported